Nuclear magnetic resonance in bipolar affective disorders. - Rangel-Guerra, R A; Perez-Payan, H; Minkoff, L; Todd, L E (American Journal of Neuroradiology, 1983)
Nuclear magnetic resonance produced by a FONAR QED 80 whole-body scanner with measurement in vivo of T1 proton relaxation time was used in 20 patients with the clinical diagnosis of bipolar affective disorder. Diagnoses were based on Research Diagnostic Criteria, Diagnostic Statistical Manual III code 296.66, and on Schedule for Affective Disorders and Schizophrenia. Proton T1 relaxation times were measured in all patients and in 18 normal controls before and after lithium carbonate treatment. Normal values of T1 in frontal and temporal lobes were 210 +/- 10 msec. All but three patients had prelithium T1 values higher than the controls (264 +/- 8.8 msec). After lithium therapy of 900 mg/day for 10 days, serum lithium levels were in the therapeutic range of 0.5-1.5 mEq/L, and patient T1 values were near normal levels (208 +/- 8.0 msec). One patient with a prelithium level within normal range proved to have cyclothymic disorder and not bipolar affective disorder; two patients did not complete the study. This study shows a statistically significant difference (p less than 0.01) in the behavior of hydrogen protons in bipolar affective disorder, which has not previously been reported in medical literature.